Spin Selectivity in Chiral Hybrid Cobalt Halide Films with Ultrasmooth Surface. Issue 12 (20th November 2022) - Wang, Qian; Lu, Ying; He, Rui‐Lin; Chen, Ruyi; Qiao, Leilei; Pan, Feng; Yang, Zhou; Song, Cheng
Abstract: Introducing chirality into low‐dimensional hybrid organic–inorganic halides (HOIHs) creates brand‐new opportunities for HOIHs in spintronics and spin‐related optoelectronics owing to chirality‐induced spin selectivity (CISS). However, preparing smooth films of low‐dimensional HOIHs with small roughness is still a great challenge due to the hybrid and complex crystal structure, which severely inhibits their applications in spintronic devices. Exploring new lead‐free chiral HOIHs with both efficient spin selectivity and excellent film quality is urgently desired. Here, cobalt‐based chiral metal halide crystals ( R / S ‐NEA)2 CoCl4 constructed by 0D [CoCl4 ] tetrahedrons and 1‐(1‐naphtyl)ethylamine (NEA) are synthesized. The orderly configuration of NEA molecules stabilized by noncovalent CH···π interaction endows (NEA)2 CoCl4 with good film‐forming ability. (NEA)2 CoCl4 films exhibit strong chiroptical activity ( g CD ≈ 0.05) and significant spin‐polarized transport (CISS efficiency up to 90%). Furthermore, ultrasmooth films (roughness ∼ 0.3 nm) with enhanced crystallinity can be achieved by incorporating tiny amount tris(8‐oxoquinoline)aluminum that has analogous conjugated structure to NEA. The realization of highly efficient spin selectivity and sub‐nanometer roughness in lead‐free chiral halides can boost the practical process of low‐dimensional HOIHs in spintronics and other fields. Abstract : Chirality‐induced spin selectivity endows metal halide perovskites with application potential in spintronics, but is limited by the rough morphology of perovskite films from the spin‐coating procedure. New lead‐free air‐stable ( R / S ‐NEA)2 CoCl4 with high‐efficiency spin selectivity is synthesized, meanwhile doping conjugate matched tris(8‐oxoquinoline)aluminum (Alq3 ) molecules can realize an ultrasmooth surface with sub‐nanometer roughness, paving the way for fabrication of spintronic devices.